DNA methylomes of bovine gametes and in vivo produced preimplantation embryos. Issue 5 (14th June 2018) - Jiang, Zongliang; Lin, Jianan; Dong, Hong; Zheng, Xinbao; Marjani, Sadie L; Duan, Jingyue; Ouyang, Zhengqing; Chen, Jingbo; Tian, Xiuchun (Cindy)
Abstract: DNA methylation is an important epigenetic modification that undergoes dynamic changes in mammalian embryogenesis, during which both parental genomes are reprogrammed. Despite the many immunostaining studies that have assessed global methylation, the gene-specific DNA methylation patterns in bovine preimplantation embryos are unknown. Using reduced representation bisulfite sequencing, we determined genome-scale DNA methylation of bovine sperm and individual in vivo developed oocytes and preimplantation embryos. We show that (1) the major wave of genome-wide demethylation was completed by the 8-cell stage; (2) promoter methylation was significantly and inversely correlated with gene expression at the 8-cell and blastocyst stages; (3) sperm and oocytes have numerous differentially methylated regions (DMRs)—DMRs specific for sperm were strongly enriched in long terminal repeats and rapidly lost methylation in embryos; while the oocyte-specific DMRs were more frequently localized in exons and CpG islands (CGIs) and demethylated gradually across cleavage stages; (4) DMRs were also found between in vivo and in vitro matured oocytes; and (5) differential methylation between bovine gametes was confirmed in some but not all known imprinted genes. Our data provide insights into the complex epigenetic reprogramming of bovine early embryos, which serve as an important model for human preimplantation development. Abstract : Genome-wide gene-specific DNA methylation in bovine sperm, oocytes and preimplantation embryos.